Mapping Students' Perceptions of Mathematics Learning: A Principal Component Analysis Study - Silfia hayuningrat; Lihar Raudina Izzati; Trysa Gustya Manda; Dadang Juandi; Jihe Chen (JPP (Jurnal Pendidikan dan Pembelajaran), 2024)
This study investigated the multidimensional landscape of students' perceptions of mathematics learning using principal component analysis (PCA). Data were collected from 102 high school students (grades 9-12, mean age 16.2 years) in Indonesia. The survey, adapted from validated scales including the Fennema-Sherman Mathematics Attitudes Scales and the Attitudes Towards Mathematics Inventory, assessed various aspects of mathematics learning perceptions. Analysis revealed fifteen initial components that were subsequently consolidated into two major factors. The first factor encompassed variables related to external and environmental aspects: learning interest, parental support, motivation, difficulties, resources, school facilities, approaches, classrooms, materials, and methods. The second factor comprised internal and cognitive elements: conceptual understanding, self-confidence, learning models, anxiety, and techniques. The PCA results highlight the complex interplay between cognitive, affective, and contextual factors in mathematics learning. The findings suggest that interventions should adopt a holistic approach, addressing both environmental and cognitive dimensions. This research contributes to educational practice by identifying key areas for targeted intervention while demonstrating the effectiveness of PCA in understanding complex educational phenomena. Future studies could explore these factors' generalizability across different educational contexts and their longitudinal evolution.